Systematic Review of joint preservation limb salvage in osteosarcoma around the knee - Zheng, Kai; Yu, Xiuchun; Xu, Ming; Cui, Haocheng; Chen, Qian (Frontiers in Oncology, 2025)
IntroductionJoint preservation limb salvage (JPLS) has benefited from advancements in tumor imaging and precision surgical technologies. However, discrepancies exist between the anticipated outcomes of surgical designs and actual clinical results. This study aims to provide a clearer understanding of JPLS.MethodsA systematic search was conducted across the MEDLINE, Embase, and Cochrane Library databases from January 1, 2003, to December 31, 2023. The search utilized the following keywords: “osteosarcoma,” “bone tumor,” “limb salvage surgery,” “surgery,” “operation,” and “knee.” Inclusion criteria were: (1) publication of original studies in English; (2) clinical research pertaining to JPLS; and (3) studies offering detailed individual patient information.ResultsUltimately, 25 articles encompassing 224 patients were included. The mean age at diagnosis was 16.8 years (range 2–59 years), with the peak incidence occurring between 9 and 18 years. Male patients predominated, with a male-to-female ratio of 1.46:1. Osteosarcomas were primarily located in the distal femur (170 cases) and proximal tibia (54 cases). Resection lengths were documented for 152 patients, averaging 167.6 mm (range 55–396 mm). Notably, reconstruction methods varied: 76 patients received allograft repair, 90 underwent inactivated tumor bone replantation, and 23 patients had autologous bone reconstruction. Additionally, 35 patients underwent prosthetic reconstruction, with 17 receiving traditionally manufactured customized prostheses and 18 utilizing 3D-printed prostheses. The average Musculoskeletal Tumor Society (MSTS) score for limb function was 26.7 points. Twelve patients experienced local tumor recurrence, 39 succumbed to tumor progression, and there were 96 non-oncological complications, predominantly fractures, infections, and bone nonunion.DiscussionThis review underscores the clinical efficacy of JPLS and examines tumor resection methods, reconstruction techniques, and associated complications.